IMPROVEMENT OF EFFICACY AND SAFETY PROFILE OF SIMVASTATIN IN COMPARISON TO REFERENCE PRODUCT (ZOCOR TABLETS) USING NANOPARTICULATE FORMULATION APPROACH - Gupta, Deepak; Mandowara, Vinod; Patel, Shetul; Shelat, Pragna (International Journal of Current Pharmaceutical Research, 2016)
Objective: Simvastatin, a HMG-CoA reductase inhibitor widely used in the treatment of Hyper (dys) lipidemia causes myotoxicity and hepatotoxicity. These safety issues limit dose of Simvastatin, lead to additional monitoring of the patients as well as discontinuation of therapy. To alleviate the adverse effects and to improve efficacy and safety profile, Simvastatin was encapsulated in the nanoparticulate formulation and compared with marketed reference formulation (Zocor tablets). Methods: The nano particles (NPs) were prepared using single emulsion diffusion method and optimized for particle size, PDI, zeta potential, encapsulation efficiency. Results: The efficacy and safety of final formulation were evaluated in HFD induced hyperlipidemic albino rats. The results suggested that the NPs have significant improvement of efficacy and reduction of the toxicity in comparison to marketed reference formulation. Conclusion: By encapsulating the Simvastatin in the NPs, the 50% dose reduction can be achieved without compromising efficacy.